Correction: An ultrasound-induced MXene doped PAM–SA super-tough hydrogel. Issue 8 (15th February 2023) - Li, Keyi; Liu, Yong; Ge, Yaqing; Cao, Hongyan; Zhuang, Shujuan; Yang, Xueting; Zhao, Yanyan; Gu, Xiangling
Abstract : Correction for 'An ultrasound-induced MXene doped PAM–SA super-tough hydrogel' by Keyi Li et al., J. Mater. Chem. C, 2023, 11, 1908–1918, ; https://doi.org/10.1039/D2TC04665B .